PENGARUH DIGITAL FINANCIAL LITERACY DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN MAHASISWA UNIVERSITAS PAMULANG DI TANGERANG SELATAN PERIODE 2020-2025 - Marisa Nurhikmah; Dina Novita (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the effect of Digital Financial Literacy and Lifestyle on the Financial Behavior of students at Universitas Pamulang in South Tangerang. This research employed a quantitative approach using a survey method. The data were collected through questionnaires distributed to 100 student respondents as the research sample. The data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) using SPSS version 30. The results showed that Digital Financial Literacy had a significant effect on students’ Financial Behavior, with a t-value of -3.278 and a significance value of 0.001 < 0.05. Lifestyle also had a significant effect on students’ Financial Behavior, with a t-value of -2.941 and a significance value of 0.004 < 0.05. Simultaneously, Digital Financial Literacy and Lifestyle had a significant effect on students’ Financial Behavior, with an F-value of 25.822 and a significance value of < 0.001 < 0.05. The coefficient of determination (R²) value of 0.347 indicates that 34.7% of the variation in students’ Financial Behavior can be explained by Digital Financial Literacy and Lifestyle, while the remaining 65.3% is influenced by other factors outside the research model.